Personalized auricular vagus nerve stimulation: beat-to-beat deceleration dominates in systole-gated stimulation during inspiration - a pilot study - Tischer, Johannes; Szeles, Jozsef Constantin; Kaniusas, Eugenijus (Frontiers in Physiology, 2025)
Neuromodulation comes into focus as a non-pharmacological therapy with the vagus nerve as modulation target. The auricular vagus nerve stimulation (aVNS) has emerged to treat chronic diseases while re-establishing the sympathovagal balance and activating parasympathetic anti-inflammatory pathways. aVNS leads still to over and under-stimulation and is limited in therapeutic efficiency. A potential avenue is personalization of aVNS based on time-varying cardiorespiratory rhythms of the human body. In the pilot study, we propose personalized cardiac-gated aVNS and evaluate its effects on the instantaneous beat-to-beat intervals (RR intervals). Modulation of RR is expected to reveal the aVNS efficiency since the efferent cardiac branch of the stimulated afferent vagus nerve governs the instantaneous RR. Five healthy subjects were subjected to aVNS. Each subject underwent two 25-min sessions. The first session started with the non-gated open-loop aVNS, followed by the systole-gated closed-loop aVNS, then the non-gated, diastole-gated, and non-gated aVNS, each for 5min. In the second session, systole and diastole gated aVNS were interchanged. Changes in RR are analysed by comparing the prolongation of RR intervals with respect to the proceeding RR interval where aVNS took place. These RR changes are considered as a function of the personalized stimulation onset, the stimulation angle starting with R peak. The influence of the respiration phases is considered on the cardiovagal modulation. The results show that the systole-gated aVNS tends to prolong and shorten RR when stimulated after and before the R peak, respectively. The later in time is the stimulation onset within the diastole-gated aVNS, the longer tends to be the subsequent RR interval. The tendency of the RR prolongation raises with increasing stimulation angle and then gradually levels off with increasing delay of the considered RR interval from the one where aVNS took place. The slope of this rise is larger for the systole-gated than diastole-gated aVNS. When considering individual respiration phases, the inspiratory systole-gated aVNS seems to show the largest slope values and thus the largest cardiovagal modulatory capacity of the personalized time-gated aVNS. This pilot study indicates aVNS capacity to modulate the heartbeat and thus the parasympathetic activity which is attenuated in chronic diseases. The modulation is highest for the systole-gated aVNS during inspiration.